Impact of the Amyotrophic Lateral Sclerosis Disease on the Biomechanical Properties and Oxidative Stress Metabolism of the Lung Tissue Correlated With the Human Mutant SOD1G93A Protein Accumulation - Aydemir, Duygu; Malik, Anjum Naeem; Kulac, Ibrahim; Basak, Ayse Nazli; Lazoglu, Ismail; Ulusu, Nuriye Nuray (Frontiers in Bioengineering and Biotechnology, 2022)
Amyotrophic lateral sclerosis (ALS) is the most common motor neuron disease, and ALS incidence is increasing worldwide. Patients with ALS have respiratory failure at the disease's end stages, leading to death; thus, the lung is one of the most affected organs during disease progression. Tissue stiffness increases in various lung diseases because of impaired extracellular matrix (ECM) homeostasis leading to tissue damage and dysfunction at the end. According to the literature, oxidative stress is the major contributor to ECM dysregulation, and mutant protein accumulation in ALS have been reported as causative to tissue damage and oxidative stress. In this study, we used SOD1G93A and SOD1WT rats and measured lung stiffness of rats by using a custom-built stretcher, where H&E staining is used to evaluate histopathological changes in the lung tissue. Oxidative stress status of lung tissues was assessed by measuring glucose 6-phosphate dehydrogenase (G6PD), 6-phosphogluconate dehydrogenase (6-PGD), glutathione reductase (GR), glutathione s-transferase (GST), catalase (CAT), and superoxide dismutase 1 (SOD1) levels. Western blot experiments were performed to evaluate the accumulation of the SOD1G93A mutated protein. As a result, increased lung stiffness, decreased antioxidant status, elevated levels of oxidative stress, impaired mineral and trace element homeostasis, and mutated SOD1G93A protein accumulation have been found in the mutated rats even at the earlier stages, which can be possible causative of increased lung stiffness and tissue damage in ALS. Since lung damage has altered at the very early stages, possible therapeutic approaches can be used to treat ALS or improve the life quality of patients with ALS.